2023
DOI: 10.21203/rs.3.rs-2559209/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and clinical impact of frailty in COPD:A Systematic Review and Meta-analysis

Abstract: Background: Frailty has been increasingly identified as a risk factor of adverse outcomes in chronic obstructive pulmonary disease (COPD). The prevalence and impact of frailty on health outcomes in people with COPD require clarification. Methods: PubMed, Embase, The Cochrane Library and Web of Science (January 1, 2002, to July 1, 2022) were comprehensively searched to identify studies related to frailty and COPD. Comparisons were made between people who did and did not have frailty for pulmonary function, dysp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…We used the independent sample t-test to determine their corresponding critical ratios, with the critical ratio < 3.0 as the deletion criteria; 2) Correlation coefficient method: We analyzed the correlation between the item and the scale score, with the correlation coefficient < 0.4 as the deletion criteria; 22 Cronbach's α coefficient method: If the total score had a relatively higher Cronbach's α coefficient after an item was deleted, this suggested that the attribute of the item to be measured in the scale was different from that of other items, and was deleted; 23 4) Factor analysis: This involved two indicators, namely "communality" and "factor load based on which we analyzed the relationship between the item and the scale; when the factor load value was <0.4 or common load occurred, the item was deleted. 24 Validity Evaluation 1) Content validity: 10 medical experts from the intervention department or hepatological surgery department were invited to evaluate the content validity. We ensured balance in age, work experience, designation, education level, and other aspects when selecting them.…”
Section: Statistical Analysis Item Analysismentioning
confidence: 99%
“…We used the independent sample t-test to determine their corresponding critical ratios, with the critical ratio < 3.0 as the deletion criteria; 2) Correlation coefficient method: We analyzed the correlation between the item and the scale score, with the correlation coefficient < 0.4 as the deletion criteria; 22 Cronbach's α coefficient method: If the total score had a relatively higher Cronbach's α coefficient after an item was deleted, this suggested that the attribute of the item to be measured in the scale was different from that of other items, and was deleted; 23 4) Factor analysis: This involved two indicators, namely "communality" and "factor load based on which we analyzed the relationship between the item and the scale; when the factor load value was <0.4 or common load occurred, the item was deleted. 24 Validity Evaluation 1) Content validity: 10 medical experts from the intervention department or hepatological surgery department were invited to evaluate the content validity. We ensured balance in age, work experience, designation, education level, and other aspects when selecting them.…”
Section: Statistical Analysis Item Analysismentioning
confidence: 99%